1993
DOI: 10.1590/1809-43921993231014
|View full text |Cite
|
Sign up to set email alerts
|

Perfil Nutricional De Pré-Escolares E Escolares Residentes Em Palmeiras Do Javari, Am

Abstract: Avaliou-se o perfil nutricional de 26 crianças em idade pré-escolar (2-5 anos) e 56 crianças em idade escolar (6-14 anos), residentes em Palmeiras do Javari, AM. Na caracterização do estado nutricional da população estudada, utilizou-se os parâmetros antropométricos, inquérito alimentar recordatório de 24 horas em conjunto com o da pesagem direta dos alimentos, determinação da hemoglobina e o parasitológico. Os resultados indicaram que dos 26 pré-escolares estudados, 11,5% apresentavam desnutrição de grau I. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
6

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
1
0
6
Order By: Relevance
“…Nestas últimas décadas, a análise evolutiva dos inquéritos nutricionais realizados na Região Amazônica evidencia uma relativa adequação protéica, com alguns grupos populacionais recebendo praticamente o dobro da recomendação. Entretanto, o aporte energético foi extremamente limitante (Lowestein,1967;Amoroso, 1981;Shrimpton, 1973Shrimpton, -1974Marinho, 1989;Nagahama et al, 1990;Rocha, 1991;1993;Yuyama et al, 1997;1998; (Tab. 3).…”
Section: Resultsunclassified
“…Nestas últimas décadas, a análise evolutiva dos inquéritos nutricionais realizados na Região Amazônica evidencia uma relativa adequação protéica, com alguns grupos populacionais recebendo praticamente o dobro da recomendação. Entretanto, o aporte energético foi extremamente limitante (Lowestein,1967;Amoroso, 1981;Shrimpton, 1973Shrimpton, -1974Marinho, 1989;Nagahama et al, 1990;Rocha, 1991;1993;Yuyama et al, 1997;1998; (Tab. 3).…”
Section: Resultsunclassified
“…Contemporary research on food consumption among indigenous peasants, also called caboclos or ribeirinhos (Moran 1974(Moran , 1991Parker 1985, for a recent debate see Adams et al 2006), have identified several patterns which may be generalized to the whole region: heavy dependence on regional staple food items (e.g., manioc and fish); increasing dependence on commercial and/or imported products; high protein consumption relative to calories; high seasonal variety of secondary food items; and the possible appearance of an epidemic pattern, characterized by the overlap of moderate states of malnutrition and chronic diseases related to changes in food habit and activity level (e.g., obesity and diabetes, among others) (Adams 2002;Adams et al 2005;Giugliano et al 1981Giugliano et al , 1984Murrieta and Dufour 2004;Murrieta et al 1999Murrieta et al , 2004Murrieta 1998Murrieta , 1999Rocha et al 1993;Silva et al 2006). Additional factors have influenced food consumption patterns over the last three decades in Amazonia, including the explosive growth of urban areas promoted at least partially by the decline of traditional subsistence activities such as extraction of forest products (e.g., rubber, gums, and fibers) and shifting cultivation (manioc), as well as by the intensification of commercial large-scale fishing and logging elsewhere (McGrath et al 1993;Padoch et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Embora alta, a prevalência de anemia nos indivíduos estudados mostrou-se menor do que a observada anteriormente, 53,5% 36 . O fato de não ter sido observada diferença nos valores de Hb entre os gêneros confirma relato de Norton et al 37 para a mesma faixa etária.…”
Section: Discussionunclassified